Formal Specification Languages: Features, Challenges and Future Directions - Ahmed, Hussin; Hussain, Azham; Baharom, Fauziah (International Journal of Engineering and Technology, 2018)
Natural language is used as a popular way for Software Requirements Specification (SRS) to ensure successful communication between stakeholders. However, natural language suffers from ambiguity which motivated software community to devise Formal Specification Languages (FSLs) to state requirements precisely. Since the advent of FSLs, a heated debate among researchers and practioners was raised to judge on the practical use of FSLs in industry. In this research, a contemporary review is conducted to shed light upon the features, challenges and future directions of FSLs.Â Â